Vytápění polyfunkčního objektu - Štěpánek, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2012)
Cílem bakalářské práce na téma „Vytápění polyfunkčního objektu“ je správné navrhnutí vytápění a funkčnost. Objekt má pět samostatných pater. Je zde navržen dvouokruhový kotel s napojením na otopná tělesa a podlahové vytápění. Dále teplovzdušné vytápění v komerčních částech.

The topic of this bachelor thesis „Heating of the multi-functional building“ is proper heating and propose functionality. The building has five separate floors. There is proposed double-circuit boiler connection to radiators and underfloor heating. Warm air heating in commercial part of building.
Heating of the Multi-functional Building
Keywords: Návrh zdroje tepla; podlahové vytápění; teplovzdušné vytápění.; Design source of heat; underfloor heating; hot-air heating.